2004
DOI: 10.1073/pnas.0401227101
|View full text |Cite
|
Sign up to set email alerts
|

The change of the brain activation patterns as children learn algebra equation solving

Abstract: In a brain imaging study of children learning algebra, it is shown that the same regions are active in children solving equations as are active in experienced adults solving equations. As with adults, practice in symbol manipulation produces a reduced activation in prefrontal cortex area. However, unlike adults, practice seems also to produce a decrease in a parietal area that is holding an image of the equation. This finding suggests that adolescents' brain responses are more plastic and change more with prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
87
1
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 119 publications
(98 citation statements)
references
References 40 publications
5
87
1
5
Order By: Relevance
“…There were two regions that had been identified by previous studies by our group Qin et al, 2004), and three parietal regions that had been identified in the triple-code theory of numerical processing by Dehaene and colleagues (see Dehaene et al, 2003, for a review). Consistent with our previous research, we generated 5 5 4 voxel regions for the ACT-R ROIs (see, e.g., Qin et al, 2004). Using the coordinates from a meta-analysis by Dehaene et al (2003, left hemisphere only), we generated 4 4 4 voxel ROIs for HIPS, PSPL, and angular gyrus.…”
Section: Fmri Analyses-onset Locking and Event Lockingmentioning
confidence: 93%
See 1 more Smart Citation
“…There were two regions that had been identified by previous studies by our group Qin et al, 2004), and three parietal regions that had been identified in the triple-code theory of numerical processing by Dehaene and colleagues (see Dehaene et al, 2003, for a review). Consistent with our previous research, we generated 5 5 4 voxel regions for the ACT-R ROIs (see, e.g., Qin et al, 2004). Using the coordinates from a meta-analysis by Dehaene et al (2003, left hemisphere only), we generated 4 4 4 voxel ROIs for HIPS, PSPL, and angular gyrus.…”
Section: Fmri Analyses-onset Locking and Event Lockingmentioning
confidence: 93%
“…Modules represent various perceptual and motor modalities, such as vision and finger manipulation, and aspects of central cognition, such as retrieving memories, cognitive control, and the maintenance of internal representations. Recent refinements of the theory involve linking the modules to specific cortical regions (Anderson, 2007;Anderson et al, 2003;Qin et al, 2004;Qin et al, 2003). Two modules were of particular interest in the present study: the retrieval module, which is identified with the lateral inferior prefrontal cortex (LIPFC), and the imaginal module, which is identified with the posterior parietal cortex (PPC).…”
Section: Modeling Reordered Calculation Strategies In a Cognitive Arcmentioning
confidence: 99%
“…For the tasks in the present study, the differential engagement was mainly due to the differences in retrieval and maintenance demands between the two strategies. Two modules were thus of particular interest in this study: the retrieval module, which is responsible for the retrieval of declarative memories and linked to the lateral inferior prefrontal cortex (LIPFC) and the imaginal module, which is responsible for the encoding and maintenance of internal representation of the problems and linked to the posterior parietal cortex (PPC) (Anderson, 2007;Qin et al, 2004). As the procedural strategy incurs more demands of retrieval and maintenance, thus, we expected LIPFC and PPC have a greater response to the procedural strategy (used in letter series tasks) than the retrieval strategy (used in number series tasks).…”
Section: Introductionmentioning
confidence: 99%
“…These findings and many others (e.g., [37,38]) have implicated the prefrontal cortex -or, more specifically, rostrolateral prefrontal cortex (RLPFC) -in higher-order relational reasoning. There is some evidence that mathematical reasoning follows the same pattern [39,40], indicating that the frontoparietal reasoning network may be domain-general [41].…”
Section: Neurodevelopment Of Reasoningmentioning
confidence: 99%